Denitrification-induced carbonate precipitation by bio-composite material with Pseudomonas aeruginosa for simultaneous nitrate and cadmium remediation. Issue 2 (7th February 2023) - Fang, Chaolin; Lin, Ruitao; Xu, Kaixuan; Achal, Varenyam
Abstract: The presence of nitrate and heavy metals in wastewater are common but serious problem throughout the world. Thus, considering their toxicity, in the present study, denitrification-induced carbonate precipitation by Pseudomonas aeruginosa was researched in the simultaneous removal of nitrate and cadmium. Prior to the experimentation, P. aeruginosa was immobilized in bio-composite material (BCM) comprised of varying concentration of bentonite and alginate. The BCM with formulation 3% (m/v) bentonite and 1% (m/v) alginate (BA3) was found to more sustained and controlled release of bacterial cells in the solution, thus was utilized for bioremediation studies. The BCM with formulation BA3 effectively removed nitrate and Cd 2+ by 93 and 74% (m/m), when their initial concentrations were 100 and 5 mg/L, respectively, in 24 h. Further, the P. aeruginosa cells inside the BCM were able to produce nitrite reductase and nitrate reductase in the spiked solution. Based on experimental results, denitrification by BCM reduced nitrate, generated alkalinity, and formed bicarbonate ions that, when reacting with Cd 2+ ions, formed cadmium carbonate. The research presented in this study is important to know the significance of bio-composite material with denitrifiers in actively producing key enzymes of denitrification leading to simultaneous removal of nitrate and heavy metal from water.